2018
DOI: 10.1182/bloodadvances.2017010348
|View full text |Cite
|
Sign up to set email alerts
|

IMiD compounds affect CD34+ cell fate and maturation via CRBN-induced IKZF1 degradation

Abstract: Key Points• IMiD compounds cause selective ubiquitination and degradation of IKZF1 in CD34 1 cells by the CRBN E3 ubiquitin ligase.• Loss of IKZF1 is associated with a decrease of PU.1, critical for the development and maturation of neutrophils.We have previously shown that immunomodulatory drug (IMiD) compounds induce a shift into immature myeloid precursors with a maturational arrest and subsequent neutropenia.The mechanism of action is unknown. Here we found that IMiD compounds cause selective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The most common AE (all grade and grade 3/4) observed with avadomide was neutropenia, which results from Ikaros degradation in myeloid cells, leading to a maturation arrest at a promyelocyte stage. 56 The introduction of an intermittent 5/7-day dosing schedule improved tolerability and reduced the frequency and severity of AEs while maintaining the clinical activity of avadomide. We recently reported that lenalidomide-mediated degradation of Ikaros in an in vitro model of myeloid differentiation results in a reversible arrest in neutrophil maturation, which is released upon removal of the drug, without any loss of cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…The most common AE (all grade and grade 3/4) observed with avadomide was neutropenia, which results from Ikaros degradation in myeloid cells, leading to a maturation arrest at a promyelocyte stage. 56 The introduction of an intermittent 5/7-day dosing schedule improved tolerability and reduced the frequency and severity of AEs while maintaining the clinical activity of avadomide. We recently reported that lenalidomide-mediated degradation of Ikaros in an in vitro model of myeloid differentiation results in a reversible arrest in neutrophil maturation, which is released upon removal of the drug, without any loss of cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was isolated with TRIZOL reagent and cDNA generated with SuperScript III reverse transcriptase (Cat#18080400; Invitrogen, Grand Island, NY), followed by Taqman (Invitrogen) based real-time polymerase chain reaction assays (Cat# 4352042; Invitrogen, Grand Island, NY) performed as described 3 , 7 , 41 . TaqMan® Gene Expression Assay (Cat# 4331182) was used for m-Pd-1h: Mm00472314_m1; m Dc-stamp: Mm04209236_m1; m-beta-actin: Mm00607939_s1.…”
Section: Methodsmentioning
confidence: 99%
“…In POMdex treated patients, the incidence of grade 3/4 neutropenia was ~50% [ 40 , 41 ]. Recent studies on molecular mechanisms of IMiD agent-mediated myelosuppression showed LEN and POM reduced PU.1 expression in CD34 + cells, leading to maturation arrest of myeloid precursors, and subsequent neutropenia [ 42 , 43 ]. The PU.1 decreased expression in CD34 + cells following IMiD exposure was found to be Ikaros-mediated and the subsequent maturation arrest at the promyelocyte stage shown to be reversible [ 44 ].…”
Section: Mechanism-driven Adverse Eventsmentioning
confidence: 99%
“…The PU.1 decreased expression in CD34 + cells following IMiD exposure was found to be Ikaros-mediated and the subsequent maturation arrest at the promyelocyte stage shown to be reversible [ 44 ]. In additional myelosuppression studies, the reduction of GATA1 expression by IMiD agents led to arrest in megakaryocyte precursors impacting thrombocytopenia [ 42 , 43 ].…”
Section: Mechanism-driven Adverse Eventsmentioning
confidence: 99%